(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Employee retention is a process that any organizations utilize to pave the ways for employees to stay with organizations for a long time. According to Jim Collins “Great vision without great people is irrelevant”. Organizations just follow it.Organizations run smoothly and face challenges efficiently with the help of good people. So, it is necessary to introduce better retention policy. In business management term, “Employee retention” refers to efforts of an employer for retaining current employees in the organization. An efficient employee retention program makes the current employees committed to their current employer. Such an employee retention program develops an environment through the correct types of policies and practices where various needs of the employees are taken care of. In the education sector India, employee retention is considered one of the biggest challenges for employers. This study finds challenging responsibilities and job satisfaction is two prime parameters in employee retention. We have attempted through this study to focus on various reasons of high faculty turnover in India and strategies that management can apply to increase faculty retention.